Sex-related differences in spontaneous intracerebral hemorrhage outcomes: A prognostic study based on 111,112 medical records - Zhao, Jieyi; Zhang, Tao; Wan, Hongli; Yu, Yang; Wen, Jin; Wang, Xiaoyu (Frontiers in Neurology, 2022)
Background and Purpose: Sex difference in nervous system disease outcomes is drawing increasing attention, but it is still ambiguous to identify the effects of sex on outcomes of spontaneous intracerebral hemorrhage. Our purpose is to determine whether the sex difference exists in the outcome of hospitalized patients with spontaneous intracerebral hemorrhage (SICH), and propose some possible causal pathways between sex and SICH outcome. Methods: A total of 111,112 SICH in-hospital patients’ medical records were collected. The mixture of data- and expert-driven techniques, the built of multivariate logistic regression model and the causal mediation analysis were used to determine the confounders and mediators, estimate the true effect of sex on SICH outcome and estimate the average proportion of causal mediation effect (CME) for each mediator. Results: (1) The failure (disability or death) rates of women in SICH outcome were significantly lower than men. On the day of discharge, the odds ratio (OR) of failure between women and men was 0.9137 (95% CI 0.8879-0.9402), while the OR at 90-day post discharge was 0.9353 (95% CI 0.9121-0.9591). (2) The sex difference in SICH outcome attenuated when age increased, and disappeared after 75 years old. (3) Deep coma, brainstem hemorrhage and infratentorial hemorrhage volume>10 ml account for 62.76% (P<0.001), 33.46% (P<0.001) and 11.56% (P<0.001) of the overall effect on the day of discharge, as well as 52.28% (P<0.001), 27.65% (P<0.001) and 10.86% (P<0.001) of that overall effect at 90-day post discharge. Conclusions: The failure risk in men was higher than women, which could be partially mediated with a higher risk for deep coma, brainstem hemorrhage and infratentorial hemorrhage volume>10 ml. It is necessary to explore some biological mechanisms which facilitate understand this difference.